Evaluating a centralised cancer support centre in the remote region of Northern Norway - Ervik, Bente; Andersen, Sigve; Skirbekk, Helge; Dønnem, Tom (Rural and Remote Health, 2020)
Introduction: Being diagnosed with cancer and undergoing treatment is a life-changing experience, and many cancer patients find the physical, emotional and social effects of the disease to be stressful. This study explores the experiences of cancer patients and their relatives from all parts of Northern Norway visiting the centralised cancer support centre. Methods: In a comprehensive prospective survey, 286 visitors were invited to participate and 181 of these accepted. The characteristics of the participants, their expectations for visiting the centre, whether they wanted to meet peers or volunteers rather than clinicians and how they viewed the centre in the context of cancer care were evaluated. Results: Most satisfied were visitors aged less than 50 years, women and those reporting a ‘strong social network’. The majority of the visitors wanted to have better access to peers (with a similar cancer diagnosis) (89%), cancer nurses (75%) or oncologists (71%). About a third of the participants (29.8%) lived in communities with fewer than 5000 inhabitants and 59.4% in municipalities with fewer than 15 inhabitants/km2. There were no significant differences in the characteristics of the participants, or in their evaluation of the support centre, when stratified by number of inhabitants or population density in their home community. Conclusion: The cancer support centre was highly valued by patients and their relatives for meeting peers. The centre was most frequently visited by and most popular among women and those self-reporting strong social networks. Access to oncology doctors and nurses in this setting could be valuable. Participants living in remote areas had similar characteristics and evaluated the support centre similarly to those living in more urban areas.